Lithium ion battery diaphragm, preparation method of lithium ion battery diaphragm and lithium ion battery using lithium ion battery diaphragm

By adopting a sandwich structure of the first porous substrate layer, the lithium-carrying layer and the second porous substrate layer in the lithium-ion battery separator, the problem of high energy consumption and long time in the water removal process of the existing lithium-ion battery is solved, and more efficient moisture removal is achieved, and battery performance and safety are improved.

CN119764760AActive Publication Date: 2025-04-04BYD CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411158551.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2025-04-04
Estimated Expiration
2044-08-21

AI Technical Summary

Technical Problem

Existing lithium-ion batteries consume high energy and have a long time during the water removal process, and have poor water removal effect, which affects battery performance and safety.

Method used

A lithium-ion battery separator is used, and its structure includes a first porous matrix layer, a lithium-carrying layer and a second porous matrix layer. The lithium-carrying layer is composed of lithium element and/or carbon-coated lithium element, and is formed by rolling and composited with the second porous matrix layer to form a sandwich structure.

Benefits of technology

This diaphragm can effectively prevent the reaction between moisture and lithium salts in the electrolyte to produce hydrofluoric acid, avoid reduced battery capacity and cycle life, battery expansion and liquid leakage, and improve battery performance and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764760A_ABST
    Figure CN119764760A_ABST
Patent Text Reader

Abstract

The invention relates to a lithium ion battery diaphragm, a preparation method of the lithium ion battery diaphragm and a lithium ion battery using the lithium ion battery diaphragm. The lithium ion battery diaphragm comprises a first porous matrix layer, a lithium carrying layer and a second porous matrix layer which are stacked in sequence, the lithium-loaded layer comprises a lithium elementary substance and / or a carbon-coated lithium elementary substance. The lithium ion battery diaphragm disclosed by the invention can react with water and HF in the battery, so that the battery capacity and cycle life are prevented from being reduced, the battery is prevented from expanding, the impedance is increased and the battery leaks.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of lithium ion battery preparation, and in particular, to a lithium ion battery separator and a preparation method thereof, and a lithium ion battery using the same. Background Art

[0002] The rapid development of new energy vehicles has put more and more urgent demands on high safety, high rate, high energy density and long cycle life of power batteries. Water is one of the key factors affecting battery performance, because it will cause a series of reactions after contact with the electrolyte, increase the resistance of lithium batteries, reduce battery capacity and life, cause battery swelling and leakage, and have a huge impact on the performance and safety of lithium batteries.

[0003] The current mainstream method of dehydration is to bake the battery at high temperature before injecting liquid to reduce the moisture content in the positive and negative electrodes; there are also solutions that use lithium replenishment and battery dehydration at the same time. However, the baking dehydration method has high energy consumption, and the baking temperature exceeds 100°C; it takes a long time, especially for silicon negative electrode plates, which require baking for more than 24 hours; and it can only remove part of the moisture in the plate, and there is still a lot of moisture left in the plate, which slowly enters the electrolyte after injection and reacts, affecting battery performance. Although the solution of replenishing lithium and dehydrating the battery at the same time can play a dehydration role during injection, the lithium enters the negative electrode for storage after injection, and the dehydration effect basically disappears. The remaining moisture in the plate and electrolyte will still cause problems such as increased battery impedance, decomposition of lithium salts, corrosion and leakage of the battery shell, affecting battery performance and safety. Summary of the invention

[0004] The purpose of the present disclosure is to provide a lithium-ion battery separator and a preparation method thereof and a lithium-ion battery using the same. The lithium-ion battery separator of the present disclosure can prevent moisture from reacting with lithium salts in an electrolyte to produce hydrofluoric acid, so as to avoid reduction in battery capacity and cycle life, battery expansion, increased impedance and battery leakage.

[0005] In order to achieve the above-mentioned object, the present disclosure provides a lithium-ion battery separator in a first aspect, wherein the lithium-ion battery separator comprises a first porous substrate layer, a lithium-carrying layer and a second porous substrate layer stacked in sequence; The lithium-carrying layer includes lithium element and / or carbon-coated lithium element.

[0006] Optionally, the lithium-carrying layer has a thickness of 1-20 μm and a surface density of 0.1-1 g / m².

[0007] Optionally, the content of Li element in the carbon-coated lithium single substance is greater than 90 wt %.

[0008] Optionally, the first porous substrate layer includes a first base membrane layer, an optional first ceramic coating layer and an optional first organic coating layer stacked in sequence, and the first ceramic coating layer and the first organic coating layer are arranged between the first base membrane layer and the lithium-carrying layer; The second porous matrix layer includes a second base membrane layer, an optional second ceramic coating layer and an optional second organic coating layer which are stacked in sequence, and the second ceramic coating layer and the second organic coating layer are arranged between the second base membrane layer and the lithium-carrying layer.

[0009] Optionally, the first base film layer and the second base film layer include polyethylene and / or polypropylene respectively; The first ceramic coating and the second ceramic coating respectively include one or more of aluminum oxide, silicon dioxide and magnesium hydroxide; The first organic coating and the second organic coating respectively include one or more of polyvinylidene fluoride, polymethyl methacrylate and polyacrylonitrile.

[0010] Optionally, the first porous matrix layer has a thickness of 10-45 μm and a porosity of 20-60%.

[0011] Optionally, the second porous matrix layer has a thickness of 10-45 μm and a porosity of 20-60%.

[0012] Optionally, the thickness of the lithium-ion battery separator is 20-110 μm.

[0013] The second aspect of the present disclosure provides a method for preparing a lithium-ion battery separator, the method comprising: rolling to form a lithium-carrying layer on a first porous substrate layer, and then compounding a second porous substrate layer on the lithium-carrying layer; The lithium-carrying layer includes lithium element and / or carbon-coated lithium element.

[0014] Optionally, the thickness of the first porous matrix layer is 10-45 μm, and the porosity is 20-60%; Optionally, the second porous matrix layer has a thickness of 10-45 μm and a porosity of 20-60%; Optionally, the first porous substrate layer includes a first base membrane layer, an optional first ceramic coating layer and an optional first organic coating layer stacked in sequence, and the first ceramic coating layer and the first organic coating layer are formed between the first base membrane layer and the lithium-carrying layer; The second porous substrate layer comprises a second base membrane layer, an optional second ceramic coating layer and an optional second organic coating layer which are stacked in sequence, wherein the second ceramic coating layer and the second organic coating layer are formed between the second base membrane layer and the lithium-carrying layer; Optionally, the first base film layer and the second base film layer include polyethylene and / or polypropylene respectively; The first ceramic coating and the second ceramic coating respectively include one or more of aluminum oxide, silicon dioxide and magnesium hydroxide; The first organic coating and the second organic coating respectively include one or more of polyvinylidene fluoride, polymethyl methacrylate and polyacrylonitrile.

[0015] Optionally, the thickness of the lithium-carrying layer is 1-20 μm; Optionally, the content of Li element in the carbon-coated lithium single substance is greater than 90 wt %.

[0016] Optionally, the rolling is performed under the condition of a dew point of below -30°C and a pressure of 0.1-1 MPa.

[0017] A third aspect of the present disclosure provides a lithium-ion battery separator prepared by the method described in the second aspect of the present disclosure.

[0018] A fourth aspect of the present disclosure provides a lithium ion battery, comprising a positive electrode, a negative electrode, an electrolyte, and the lithium ion battery separator according to the first aspect or the third aspect of the present disclosure.

[0019] Through the above technical solution, the diaphragm disclosed in the present invention has a sandwich structure of "first porous matrix layer + lithium-carrying layer + second porous matrix layer". The lithium-carrying layer exists between the two porous matrix layers. Li does not contact the positive and negative electrodes, nor does it enter the negative electrode for storage, and exists in the electrolyte for a long time. During the battery injection process, the injected electrolyte contacts the diaphragm, and the water and HF in the electrolyte react with the metal Li in the lithium-carrying layer of the diaphragm. The generated gas is discharged out of the battery to avoid the subsequent reaction of water and HF in the electrolyte to produce gas inside the battery, causing the battery to swell or even crack. The metal Li in the lithium-carrying layer can react with water and HF in the battery to avoid the consumption of active lithium ions by water and slow down the reduction of battery capacity. In addition, it can also prevent HF from damaging the SEI film and the generation of POF on the surface of the SEI film. 3 The HF content in the battery is reduced, which avoids corrosion of the battery shell and reduces the risk of battery leakage and failure. The Li in the diaphragm does not contact the positive and negative electrodes, which can play a role in continuous water removal, slowing down the adverse effects of battery capacity decline, cycle life reduction, SEI film thickening, battery impedance increase, and increased risk of leakage and failure, thereby improving battery performance.

[0020] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings: Figure 1 This is a scanning electron microscope image of the diaphragm prepared in Example 1 of the present disclosure after cycling. DETAILED DESCRIPTION

[0022] The specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.

[0023] The first aspect of the present disclosure provides a lithium-ion battery separator, which includes a first porous substrate layer, a lithium-carrying layer, and a second porous substrate layer stacked in sequence; The lithium-carrying layer includes lithium element and / or carbon-coated lithium element.

[0024] The diaphragm disclosed in the present invention has a sandwich structure of "first porous matrix layer + lithium-carrying layer + second porous matrix layer". The lithium-carrying layer exists between the two porous matrix layers. Li does not contact the positive and negative electrodes, nor does it enter the negative electrode for storage. It exists in the electrolyte for a long time, which has the following advantages: (1) Reduce battery swelling. When the battery is filled, the metal Li in the lithium-carrying layer of the diaphragm reacts with the water and HF in the electrolyte, thereby removing the water and HF in the electrolyte and generating H 2 During the formation process, the water in the electrode will gradually enter the electrolyte, and then react with the metal Li in the lithium-carrying layer of the diaphragm to produce H 2 It will also be discharged, reducing the subsequent battery volume expansion and preventing the pressure inside the battery from increasing, which may cause the battery to deform or even burst. (2) Slow down the increase of internal resistance. When the water content is higher than the content required for the system to form a SEI film, POF is generated on the surface of the SEI film. 3 The lithium in the lithium-carrying layer of the diaphragm, because it always exists in the electrolyte, not only reacts with water during the injection and formation process, but also continuously consumes the remaining water during the subsequent battery cycle and storage process, thereby reducing the increase in internal resistance; (3) Avoid capacity reduction. The water inside the battery will consume the active lithium ions in the electrolyte, causing the lithium ions to undergo irreversible chemical reactions in the negative electrode of the battery. The consumption of active lithium ions will cause the battery capacity to decrease. The metal Li in the lithium-carrying layer of the diaphragm will continuously consume the remaining water during the subsequent battery cycle and storage process, thereby reducing the water consumption of active lithium ions in the electrolyte and avoiding the reduction of battery capacity. (4) Slow down the reduction of cycle life. The water in the battery reacts with lithium salts to generate HF, which destroys the SEI film and causes secondary film formation. This cycle continues, causing battery performance to deteriorate and cycle life to decrease. The metal Li in the lithium-carrying layer of the diaphragm can continuously consume water during subsequent battery cycles and storage, preventing water from reacting with lithium salts to generate HF and then destroying the SEI film, thereby slowing down the reduction of battery cycle life; (5) Avoid battery leakage. The electrolyte inside the battery reacts with water to produce HF, which will corrode the metal parts inside the battery, causing the battery to leak, resulting in a rapid decline in battery performance. It will also corrode the devices used, causing more dangerous failures. The metal Li in the lithium-carrying layer of the diaphragm continuously consumes the remaining water during subsequent battery cycles and storage, avoiding the reaction of water and lithium salts to produce HF, preventing battery leakage, and improving battery safety.

[0025] According to one embodiment of the present disclosure, the thickness of the lithium-carrying layer is 1-20 μm, preferably 3-6 μm, including but not limited to 1 μm, 3 μm, 6 μm, 10 μm, 12 μm, 15 μm, 18 μm, and 20 μm; the surface density is 0.01-1 g / m², preferably 0.1-0.3 g / m², including but not limited to 0.01 g / m², 0.1 g / m², 0.3 g / m², 0.5 g / m², 0.53 g / m², 0.67 g / m², 0.80 g / m², 0.9 g / m², 0.95 g / m², 1 g / m², the diaphragm with the above parameters avoids blocking the pores of the first porous matrix layer and the second porous matrix layer, allowing the solvent to pass through the diaphragm smoothly, further improving the cycle life and capacity of the battery, reducing internal resistance, and reducing battery swelling. At the same time, it can avoid the poor water removal effect caused by the rapid consumption of lithium and carbon-coated lithium.

[0026] According to an embodiment of the present disclosure, the content of Li element in the carbon-coated lithium single substance is greater than 90 wt % to improve the performance of the separator.

[0027] According to one embodiment of the present disclosure, the first porous substrate layer includes a first base membrane layer, an optional first ceramic coating and an optional first organic coating which are stacked in sequence, and the first ceramic coating and the first organic coating are arranged between the first base membrane layer and the lithium-carrying layer, that is, when the first porous substrate layer includes a coating and the lithium-carrying layer is arranged on the coating, the above arrangement is conducive to the adhesion of the lithium-carrying layer; according to another embodiment, a ceramic coating and / or an organic coating may also be arranged on the side of the first porous substrate layer away from the lithium-carrying layer.

[0028] According to one embodiment of the present disclosure, the second porous substrate layer includes a second base membrane layer, an optional second ceramic coating and an optional second organic coating which are stacked in sequence, and the second ceramic coating and the second organic coating are arranged between the second base membrane layer and the lithium-carrying layer, that is, when the second porous substrate layer includes a coating and the lithium-carrying layer is arranged on the coating, the above arrangement is conducive to the adhesion of the lithium-carrying layer; according to another embodiment, a ceramic coating and / or an organic coating may also be arranged on the side of the second porous substrate layer away from the lithium-carrying layer.

[0029] According to a specific embodiment of the present disclosure, a lithium-ion battery separator includes a first base film layer, a first organic coating layer, a lithium-carrying layer, a second organic coating layer, and a second base film layer which are sequentially stacked.

[0030] According to a specific embodiment of the present disclosure, a lithium-ion battery separator includes a first base film layer, a first ceramic coating layer, a lithium-carrying layer, a second ceramic coating layer, and a second base film layer which are sequentially stacked.

[0031] According to a specific embodiment of the present disclosure, a lithium-ion battery separator includes a first base film layer, a first ceramic coating, a first organic coating, a lithium-carrying layer, a second ceramic coating, a second organic coating and a second base film layer stacked in sequence.

[0032] According to one embodiment of the present disclosure, the first base film layer and the second base film layer respectively include polyethylene and / or polypropylene, and the compositions of the first base film layer and the second base film layer are the same or different, preferably the same.

[0033] According to one embodiment of the present disclosure, the first ceramic coating and the second ceramic coating respectively include aluminum oxide (Al 2 O 3 ), silicon dioxide (SiO 2 ) and magnesium hydroxide (Mg(OH) 2 ), the compositions of the first ceramic coating and the second ceramic coating are the same or different, preferably the same.

[0034] According to one embodiment of the present disclosure, the first organic coating and the second organic coating respectively include one or more of polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA) and polyacrylonitrile (PAN), and the composition of the first organic coating and the second organic coating is the same or different, preferably the same.

[0035] According to one embodiment of the present disclosure, the thickness of the first porous matrix layer is 10~45μm, including but not limited to 10μm, 12μm, 15μm, 18μm, 20μm, 25μm, 30μm, 35μm, 40μm, and 45μm; the porosity is 20~60%, including but not limited to 20%, 30%, 35%, 40%, 42%, 50%, and 60%.

[0036] According to one embodiment of the present disclosure, the thickness of the second porous matrix layer is 10~45μm, including but not limited to 10μm, 12μm, 15μm, 18μm, 20μm, 25μm, 30μm, 35μm, 40μm, and 45μm; the porosity is 20~60%, including but not limited to 20%, 30%, 35%, 40%, 42%, 50%, and 60%.

[0037] In order to make the battery have a higher volume energy density, according to one embodiment of the present disclosure, the thickness of the lithium ion battery separator is 20~110μm, preferably 20~45μm, including but not limited to 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, 60μm, 70μm, 78μm, 85μm, 90μm, 100μm, and 110μm.

[0038] The second aspect of the present disclosure provides a method for preparing a lithium-ion battery separator, the method comprising: rolling to form a lithium-carrying layer on a first porous substrate layer, and then compounding a second porous substrate layer on the lithium-carrying layer; The lithium-carrying layer includes lithium element and / or carbon-coated lithium element.

[0039] According to one embodiment of the present disclosure, the method includes: dispersing lithium element and / or carbon-coated lithium element on a first porous matrix layer, rolling to form a lithium-carrying layer, and then composite a second porous matrix layer on the lithium-carrying layer.

[0040] According to one embodiment of the present disclosure, the first porous matrix layer includes a first base membrane layer, an optional first ceramic coating and an optional first organic coating which are stacked in sequence, and the first ceramic coating and the first organic coating are formed between the first base membrane layer and the lithium-carrying layer, that is, the lithium-carrying layer is formed on the coating.

[0041] According to one embodiment of the present disclosure, the second porous matrix layer includes a second base membrane layer, an optional second ceramic coating and an optional second organic coating which are stacked in sequence, and the second ceramic coating and the second organic coating are formed between the second base membrane layer and the lithium-carrying layer, that is, the lithium-carrying layer is formed on the coating.

[0042] In order to allow the lithium element and the carbon-coated lithium element to be completely attached to the porous matrix layer and to avoid the porous matrix layer sites corresponding to the lithium element and the carbon-coated lithium element from being crushed, according to one embodiment of the present disclosure, the rolling is carried out under the condition of a dew point below -30°C, and the pressure is 0.1~1MPa, preferably 0.1~0.4MPa, including but not limited to 0.1MPa, 0.3MPa, 0.4MPa, 0.5MPa, 0.8MPa, and 1MPa.

[0043] According to a preferred embodiment of the present disclosure, the lithium-carrying layer includes a lithium element coated with carbon, so as to facilitate the preparation of the separator.

[0044] In the present disclosure, the manner of forming the ceramic coating and the organic coating is conventional in the art.

[0045] According to one embodiment of the present disclosure, a method for compounding a second porous matrix layer on a lithium-carrying layer includes: rolling or hot pressing, and the specific conditions and steps are conventional in the art.

[0046] A third aspect of the present disclosure provides a lithium-ion battery separator prepared by the method described in the second aspect of the present disclosure.

[0047] The lithium ion battery separator described in the third aspect of the present disclosure has the same characteristics as the lithium ion battery separator described in the first aspect of the present disclosure, which will not be described in detail here.

[0048] A fourth aspect of the present disclosure provides a lithium ion battery, comprising a positive electrode, a negative electrode, an electrolyte, and the lithium ion battery separator according to the first aspect or the third aspect of the present disclosure.

[0049] According to one embodiment of the present disclosure, the positive electrode of the lithium-ion battery includes a positive electrode active material, and the positive electrode active material includes one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and olivine-structured lithium-containing phosphate.

[0050] According to one embodiment of the present disclosure, the negative electrode of the lithium-ion battery includes a negative electrode active material, which includes one or more of a carbon-based negative electrode active material, a silicon-based negative electrode active material and an intercalable lithium alloy negative electrode active material; the carbon-based negative electrode active material includes one or more of natural graphite, artificial graphite, soft carbon, hard carbon, mesophase carbon microspheres, nanocarbon and carbon fibers; the silicon-based negative electrode active material includes one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, and silicon alloys; the intercalable lithium alloy negative electrode active material includes one or more of elemental tin, tin oxide compounds, tin-carbon composites and tin alloys.

[0051] According to one embodiment of the present disclosure, the electrolyte of the lithium-ion battery contains an organic solvent, an additive and a lithium salt; the organic solvent includes one or more of ethylene carbonate, diethyl carbonate, dimethyl carbonate, propylene carbonate, ethyl methyl carbonate, methyl formate and ethyl acetate; the additive includes one or more of vinylene carbonate, vinyl sulfite, propylene sulfite, trimethyl phosphate, vinylene sulfate and fluoroethylene carbonate; the lithium salt includes one or more of lithium iron phosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium bis(trifluoromethylsulfonylimide), lithium perchlorate and lithium hexafluoroarsenate.

[0052] In the present disclosure, the methods for preparing positive electrode sheets, negative electrode sheets, electrolytes, and lithium-ion batteries using the separator of the present disclosure are conventional in the art.

[0053] The present invention will be described in detail below by way of examples, but is not limited to the following examples.

[0054] Unless otherwise specified, the reagents used in the following examples and comparative examples are commercially available.

[0055] In the Examples and Comparative Examples: Diaphragm thickness test method: Use a micrometer to measure the diaphragm thickness; Testing method for lithium-loaded layer thickness: Use a micrometer to measure the thickness of the lithium-loaded diaphragm as a, the thickness of the non-lithium-loaded diaphragm as b, and the lithium-loaded layer thickness value is ab.

[0056] Example 1) Preparation of positive electrode The positive electrode active material lithium iron phosphate (LFP), the conductive agent acetylene black and carbon nanotube (CNT), and the binder polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 96:1.5:0.5:2, and the solvent N-methylpyrrolidone (NMP) is added and stirred into a uniform positive electrode slurry (solid content is 65 weight%); the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and after oven drying, it is rolled, slit, and die-cut into positive electrode sheets.

[0057] 2) Preparation of negative electrode sheet The negative electrode active material graphite, the conductive agent acetylene black and carbon nanotubes (CNT), the binder styrene butadiene rubber (SBR), and the thickener carboxymethyl cellulose (CMC) are mixed in a weight ratio of 95.5:1:1.5:2, and deionized water is added to stir to form a uniform negative electrode slurry (solid content is 50 weight%); the negative electrode slurry is evenly coated on the negative electrode current collector copper foil, and then rolled after drying in an oven.

[0058] 3) Preparation of diaphragm With ceramic coating (aluminum oxide, Al 2 O 3) polyethylene film (thickness of 20 μm, porosity of 50%) is used as the first porous matrix layer and the second porous matrix layer; under the condition of a dew point below -30°C, a carbon-coated lithium single substance (Li element content of 92 wt%) is uniformly dispersed on the first porous matrix layer, and a roller press is used to roll the surface of the first porous matrix layer to form a lithium-carrying layer at a pressure of 0.4 Pa, and then the second porous matrix layer is composited on the lithium-carrying layer to obtain a lithium-ion battery separator. The parameters are listed in Table 1.

[0059] 4) Preparation of electrolyte Ethylene carbonate (EC), diethyl carbonate (DEC), and dimethyl carbonate (DMC) were mixed in a volume ratio of 1:1:1 and 3% by volume of vinylene carbonate (VC) was added to obtain an organic solvent. 6 Dissolve in a mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0060] 5) Preparation of batteries The positive electrode sheet, separator, and lithium-supplemented negative electrode sheet are stacked in order so that the separator is between the positive and negative electrode sheets, and then the electrode core is obtained by stacking the sheets. The electrode core is placed in an outer packaging shell, and the electrolyte is injected. After packaging, infiltration, formation, and capacity division processes, a lithium-ion battery is obtained.

[0061] Comparative Example The lithium-ion battery was prepared by the method of the embodiment, except that the separator did not contain a lithium-carrying layer, but consisted of two layers of ceramic coating (aluminum oxide, Al 2 O 3 ) polyethylene film (thickness 20μm, porosity 50%), the parameters are listed in Table 1.

[0062] Test Case For the batteries of the embodiment and the comparative example, the battery H is tested after 24 hours of injection and immersion. 2 The gas production, HF content in the battery electrolyte after 24 hours of injection and immersion, HF content in the battery electrolyte after formation, capacity retention rate after 400 cycles of the battery at 60°C, and 50% SOC discharge DCIR impedance (tested at 25°C) are listed in Table 1. The specific test method is as follows: H 2 Gas production test 1) Apply sealant to the appropriate part of the unfilled battery, inject electrolyte into the battery through the sealant using a syringe, and let the battery sit for 24 hours; 2) In the glove box, inject V into the battery using a syringe. Ar mL Ar (usually 2 mL); 3) After the argon gas is fully mixed with the gas in the battery, take out 2 mL with a syringe and quickly plug the needle with silicone to prevent gas leakage; 4) Take 1.5 mL of gas and inject it into the gas chromatograph for testing to obtain the volume ratio of hydrogen generated by the battery, n H2 , Argon volume percentage n Ar , the battery produces H 2 Capacity .

[0063] Lithium loading surface density test 1) Sampling In a dew point controlled environment (dew point < -30°C), accurately cut a certain area of ​​lithium-loaded diaphragm and place it in a glass bottle, and record the area. S DCCT and sealed with a rubber stopper and a metal cap; 2) Test the displacement volume V of the air bag 1 Take an air bag and drain the remaining gas. Hang a standard weight of 100g under the air bag. Immerse the air bag and the weight completely in deionized water. Use a balance to weigh the weight and the air bag. 1 ,but F 1 = G 1 = ρ H20 · ɡ · V 1 =(100+ m 气袋 - m 1 ) ɡ .

[0064] 3) Collect the reaction hydrogen Remove the air bag, then connect the syringe needles at both ends of the catheter with a valve, connect the two ends of the catheter to the sealed glass bottle and the air bag respectively by needle puncture, and open the valve of the catheter to connect the glass bottle and the air bag.

[0065] Extract V 2 volume of deionized water, slowly inject the deionized water into the glass bottle through a syringe, and keep 1-2ml of deionized water in the syringe. When the reaction is almost over, inject the remaining deionized water to promote the full reaction and cooling of the active lithium; slowly shake the glass bottle during the entire titration process to promote the full reaction of the lithium-loaded diaphragm and the deionized water. Control the reaction speed during the reaction and try to avoid the generation of a large amount of water vapor entering the air bag. If necessary, slow down the reaction process by cooling the reaction in a water bath.

[0066] 4) Test the volume V of the air bag after the reaction3 After the lithium-loaded diaphragm and water react completely and return to room temperature (25°C), close the valve of the catheter, remove the air bag and seal it, and hang a standard weight of 100g under the air bag. Completely immerse the air bag filled with gas and the weight in deionized water, and use a balance to weigh the mass m of the weight and air bag at this time. 3 ,but F 3 = G 3 = ρ H20 · ɡ · V 3 =(100+ m 气袋 - m 3 )× ɡ .

[0067] 5) Data processing The active lithium mass is calculated according to the following formula: Active lithium mass in lithium-carrying separator m Li =0.585*( V 3 - V 1 - V 2 ), active lithium loading L = m Li / S DCCT .

[0068] Electrolyte HF content test 1) Prepare bromothymol blue indicator: Weigh 0.18 g of bromothymol blue solid (McLean) and pour it into a cup; weigh 39.55 g of anhydrous methanol (50 mL) into the cup; stir gently to dissolve the solid and mix evenly; 2) Prepare sodium methoxide methanol solution titrant: Weigh 0.02g of sodium methoxide solid (Aladdin) and pour it into a cup; weigh 39.55g of anhydrous methanol (50mL) in the cup; stir to completely dissolve the solid and mix evenly; 3) Titration: Pour 2mL of anhydrous methanol liquid into the test cup; add two drops of bromothymol blue indicator solution (if the acidity in the electrolyte is too low or too high, add 3 or 4 drops of indicator), and the solution will be bright yellow; use sodium methoxide methanol solution to titrate the base solution in the cup to turn the solution from bright yellow to blue; Place the test cup on an analytical balance, return it to zero, add about 0.2-0.5g of the electrolyte to be tested, and record the actual amount of electrolyte added m electrolyte (in g); Return the analytical balance to zero, remove the cup and titrate the electrolyte to be tested with sodium methoxide methanol solvent, adding drop by drop and shaking while adding until the liquid in the cup changes from bright yellow to blue; Place it on the analytical balance and record the amount of sodium methoxide methanol solution titrant used m sodium methoxide (in g); 4) Calculation: HF content (ppm): m HF =m 甲醇钠 *0.0005054 / 54.02*20 / m 电解液 *1000000, simplified formula is m HF =m 甲醇钠 / m 电解液 *187.1159(M 甲醇钠 is 54.02 g / mol, M HF is 20g / mol).

[0069] Cyclic and DCIR testing The cycle test steps at high temperature 60°C are as follows: 1) The battery is placed in a 60℃ high temperature box for 6 hours; 2) 1C constant current and constant voltage charging to 3.8V, 0.05C cut-off, and leave for 10 minutes; 3) 1C constant current discharge to 2.0V, leave for 10 minutes; 4) Cycle 400 times, and perform RPT test before the cycle and after every 200 cycles.

[0070] RPT Test After the battery is left at room temperature for 6 hours, perform the RPT test: 1) Capacity test (1) Discharge, 1 / 3C constant current discharge to 2.0V, leave for 10 minutes; (2) Charging: 1 / 3C constant current and constant voltage charging to 3.8V, 0.2C cut-off, and leave for 10 minutes; (3) Discharge: 1 / 3C constant current discharge to 2.0V, leave for 10min, the capacity is recorded as C0; (2) Charging: 1 / 3C constant current and constant voltage charging to 3.8V, 0.2C cut-off, and leave for 10 minutes; 2) DCIR test (1) Adjust to 50% SOC: 1 / 3C constant current discharge 50% C0, adjust to 50% SOC, and leave for 10 minutes; (2) D_DCIR: 1.5C0 discharge for 30s; (3) Leave for 10 minutes; (4) C_DCIR: 1.5C0 charging for 30s; (5) Leave for 10 minutes; (6) 1 / 3C constant current and constant voltage discharge to 2.0V, 0.04C cut-off, and leave for 60 minutes; (7) 1 / 3C constant current and constant voltage charging to 3.8V, 0.04C cut-off, and leave for 60 minutes; (8) 1 / 3C constant current and constant voltage discharge to 2.0V, 0.04C cut-off, and leave for 60 minutes; (9) Leave for 10 minutes; Record the last voltage data of steps (1) to (4), mark them as V1, V2, V3, and V4 in sequence, and calculate the 50% SOC DCIR value according to the following formula: DCIR = (V1-V2) / 202.5*1000 (unit: mΩ); DCIR charge = (V4-V3) / 202.5*1000 (unit: mΩ).

[0071] The battery of Example 1 after cycling was disassembled to obtain the diaphragm, and a scanning electron microscope test was performed. The results are as follows: Figure 1 As shown, according to Figure 1 It can be seen that there are particles with a diameter of 10~100μm on the diaphragm. The XRD test determined that the main components of the particles are Li, Li 2 CO 3 、LiOH、Li 2 O.

[0072] Table 1

[0073] In Table 1 above, Examples 1 to 4 are the same lithium-ion batteries, and the battery H is injected and soaked for 24 hours four times. 2 Gas production and HF content of battery electrolyte after 24h injection and immersion. 2The average value of gas production is 2.111 mL, and the average value of HF content in the battery electrolyte after four injections and immersion for 24 hours is 472.5 ppm; Examples 5 to 8 are result data of HF content in the battery electrolyte after four formations of the same lithium ion battery, and the average value of HF content in the battery electrolyte after four formations is 19.75 ppm; Examples 9 to 12 are result data of 50% SOC discharge DCIR impedance at 25°C and capacity retention rate at 60°C for 400 cycles of the same lithium ion battery at 60°C, respectively. After four cycles at 60°C for 400 cycles, the average value of DCIR impedance at 50% SOC discharge at 25°C of the battery is 64.18 mΩ, and the average value of capacity retention rate after four cycles at 60°C for 400 cycles is 91.15%; the lithium ion batteries of Examples 1 to 12 have the same composition and structure.

[0074] Comparative Examples 1 to 4 are the same lithium-ion batteries, and the battery H is injected and immersed for 24 hours four times. 2 Gas production and HF content of battery electrolyte after 24h injection and immersion. 2 The gas production is 0 mL, and the average HF content of the battery electrolyte after four injections and immersion for 24 hours is 1145 ppm; Comparative Examples 5 to 8 are the result data of the HF content of the battery electrolyte after the same lithium ion batteries are formed four times, and the average HF content of the battery electrolyte after the four formations is 120.5 ppm; Comparative Examples 9 to 12 are the result data of the DCIR impedance of the battery at 50% SOC discharge at 25°C and the capacity retention rate of the battery at 60°C for 400 cycles after the same lithium ion batteries are cycled at 60°C for four times, and the average DCIR impedance of the battery at 50% SOC discharge at 25°C after four cycles at 60°C for 400 cycles is 86.9 mΩ, and the average capacity retention rate of the battery at 60°C for 400 cycles is 80.75%; the lithium ion batteries of Comparative Examples 1 to 12 have the same composition and structure.

[0075] According to the above data, the lithium-ion battery separator of the present invention can react with water and HF in the battery to avoid the consumption of lithium ions. The use of the separator to prepare lithium-ion batteries can reduce the H 2 The gas production, the HF content of the electrolyte in the battery after injection and formation, and the battery impedance after 400 cycles at 60°C were used to improve the capacity retention rate after 400 cycles at 60°C.

[0076] The preferred embodiments of the present disclosure are described in detail above; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0077] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0078] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A lithium ion battery separator, characterized in that: The lithium-ion battery separator comprises a first porous matrix layer, a lithium-carrying layer and a second porous matrix layer stacked in sequence; The lithium-carrying layer includes lithium element and / or carbon-coated lithium element.

2. The lithium ion battery separator according to claim 1, wherein The thickness of the lithium-carrying layer is 1-20 μm, and the surface density is 0.01-1 g / m².

3. The lithium ion battery separator according to claim 1, wherein The content of Li element in the carbon-coated lithium single substance is 90 wt % or more.

4. The lithium ion battery separator according to claim 1, wherein The first porous substrate layer comprises a first base membrane layer, an optional first ceramic coating layer and an optional first organic coating layer which are stacked in sequence, wherein the first ceramic coating layer and the first organic coating layer are arranged between the first base membrane layer and the lithium-carrying layer; The second porous matrix layer includes a second base membrane layer, an optional second ceramic coating layer and an optional second organic coating layer which are stacked in sequence, and the second ceramic coating layer and the second organic coating layer are arranged between the second base membrane layer and the lithium-carrying layer.

5. The lithium ion battery separator according to claim 4, wherein: The first base film layer and the second base film layer respectively include polyethylene and / or polypropylene; The first ceramic coating and the second ceramic coating respectively include one or more of aluminum oxide, silicon dioxide and magnesium hydroxide; The first organic coating and the second organic coating respectively include one or more of polyvinylidene fluoride, polymethyl methacrylate and polyacrylonitrile.

6. The lithium ion battery separator according to claim 1, wherein The first porous matrix layer has a thickness of 10-45 μm and a porosity of 20-60%.

7. The lithium ion battery separator according to claim 1, wherein The second porous matrix layer has a thickness of 10-45 μm and a porosity of 20-60%.

8. The lithium ion battery separator according to claim 1, wherein The thickness of the lithium ion battery separator is 20-110 μm.

9. A method for preparing a lithium ion battery separator, characterized in that: The method comprises: rolling and pressing a first porous matrix layer to form a lithium-carrying layer, and then compounding a second porous matrix layer on the lithium-carrying layer; The lithium-carrying layer includes lithium element and / or carbon-coated lithium element.

10. The method according to claim 9, wherein: The thickness of the first porous matrix layer is 10-45 μm, and the porosity is 20-60%; Optionally, the second porous matrix layer has a thickness of 10-45 μm and a porosity of 20-60%; Optionally, the first porous substrate layer includes a first base membrane layer, an optional first ceramic coating layer and an optional first organic coating layer stacked in sequence, and the first ceramic coating layer and the first organic coating layer are formed between the first base membrane layer and the lithium-carrying layer; The second porous substrate layer comprises a second base membrane layer, an optional second ceramic coating layer and an optional second organic coating layer which are stacked in sequence, wherein the second ceramic coating layer and the second organic coating layer are formed between the second base membrane layer and the lithium-carrying layer; Optionally, the first base film layer and the second base film layer include polyethylene and / or polypropylene respectively; The first ceramic coating and the second ceramic coating respectively include one or more of aluminum oxide, silicon dioxide and magnesium hydroxide; The first organic coating and the second organic coating respectively include one or more of polyvinylidene fluoride, polymethyl methacrylate and polyacrylonitrile.

11. The method according to claim 9, wherein: The thickness of the lithium-carrying layer is 1-20 μm; Optionally, the content of Li element in the carbon-coated lithium single substance is greater than 90 wt %.

12. The method according to claim 9, wherein: The roller pressing is performed under the condition of a dew point of below -30°C and a pressure of 0.1-1 MPa.

13. A lithium ion battery separator prepared by the method according to any one of claims 9 to 12.

14. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode, a negative electrode, an electrolyte and the lithium-ion battery separator according to any one of claims 1 to 8 and 13.

Citation Information

Patent Citations

  • Secondary battery and lithium supplementing method therefor, battery module, battery pack, and electric device

    EP4207415A1

  • A separator and electrochemical device including the same

    KR1020160032941A

  • Separator for lithium secondary battery and lithium secondary battery comprising same

    WO2018164517A1

  • Separator, electrical device comprising separator, and preparation method therefor

    WO2022021590A1